The monetisation of space - Papazian, Armen V. (Frontiers in Space Technologies, 2025)
The defining obstacle to our expansion into outer space is not technological, but conceptual. While our engineering ingenuity has already enabled extraordinary feats — from lunar landings to Martian rovers and artificial intelligence—our financial and monetary economics remain shackled to inadequate assumptions that prohibit the sustainable expansion of our footprint in outer space and drag us ever closer to the edge of an ecological catastrophe on Earth. Today, neither billionaires, corporations, nor governments are able to fund our multi-planetary or multi-habitat future. I argue that our expansion into outer space requires a fundamental rethink of our financial value framework, mathematics, and monetary architecture. To unlock the massive investments needed for outer space development and settlement, we must first integrate space as a foundational dimension of value in finance—heretofore built around risk and calendar time. The introduction of space as an analytical dimension in finance is a first step that leads to a new principle of value, the Space Value of Money (SVoM), which, in turn, triggers a profound change in our mathematics and architecture. These transformations make the monetisation of space possible, i.e., the creation of money based on space value creation. The monetisation of space is translated into systemic change through the introduction of new financial instruments designed for central bank purchase. Public Capitalisation Notes (PCNs) are proposed as a viable alternative that can help fund our sustainable multi-planetary future.